Sensors and Mini Photocatalytic Reactor as a Tool for Measure CO2 Gas from the Degradation of the Detergent Active Compound - Maryani, Yeyen; Ruhiat, Yayat; Oktarisa, Yuvita (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to test the performance and feasibility of new tools and methods for analysis of detergent based on the photocatalytic degradation of LAS and ABS, which is a detergent active compound. Testing is done by measuring the CO2 gas formed from the degradation at every one-hour for five hours of reaction. The results of the determination of analytical parameters are as follows, sensitivity: 0.394 to 0.460, the limit of detection: 0.16 mg/L, accuracy: 0.94% to 12.88% and punctilio: 0.12% to 0.14%, the range of linearity: 0.4 mg/L to 2 mg/L. Results of calibration using standard solutions obtained regression equation y = 1.033 x - 77.713 with R2 = 0.988, indicating that the instrument has been calibrated and fit for use for the analysis of LAS and ABS with concentrations above or equal to 25 mg/L. The test results showed that the developed method is practical, effective and efficient.